Discrepancies of Notch 1 receptor during development of chronic seizures. Issue 8 (21st January 2019) - Saffarzadeh, Fatemeh; Modarres Mousavi, Sayed Mostafa; Lotfinia, Ahmad Ali; Alipour, Fatemeh; Hosseini Ravandi, Hassan; Karimzadeh, Fariba
Abstract: The critical role of Notch signaling has been shown in the pathogenesis of some neurological disorders including schizophrenia, epilepsy and Alzheimer's disease. This study was aimed to evaluate the role of Notch 1 receptor in epileptogenesis as well as seizure characteristics. The animals were divided into three groups of sham, early stage and end stage. In sham group: Normal saline was injected intraperitoneally (ip) in the same as protocol of pentylenetetrazol (PTZ) injection. PTZ was injected (ip) every 48 hr over a period of 1 week in the group of early stage and over a period of 4 weeks in the end stage. The gene expression as well as distribution of Notch 1 receptor was assessed in the parietal cortex and hippocampus. In addition, the effect of agonist or antagonist of Notch 1 receptor was assessed on the epileptic discharges induced by PTZ injection. The gene expression of Notch 1 decreased in the hippocampus significantly in the end‐stage group compared with sham, and early groups. Furthermore, distribution of Notch 1 receptor increased in the somatosensory cortex and decreased in the CA1 hippocampal area in the end‐stage group. Intraventricular microinjection of Notch 1 agonist significantly increased the amplitude as well as frequency of spikes and decreased the latency of first epileptic discharges. Our findings illustrate the critical role of Notch signalling as a potential pathway in the epileptogenesis during development of chronic seizures. Abstract : 1. Notch‐signaling pathway has an important role in some developmental neurological disorders. 2. This study indicated that Notch 1 receptor involve to development of chronic seizures. 3. Our data demonstrated the pharmacological effect of Notch 1 receptor on the seizure characteristics.